Project Based DMC (Digital Marketing Channel) Learning Development to Growing DMC Ability of Management Students FEB Unisma - Eka Farida (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This study aims to produce a project-based DMC learning model and use it as a learning reference to improve the quality of learning and be able to grow students' DMC abilities. Methodology: The design of this study is a research and development model based on research. Design based research is a methodology to understand how, when, and why learning innovations are designed, implemented, and evaluated. There are four stages of activity, including identification of needs, preparing designs and prototypes, conducting validation tests and improving prototypes, perfecting the final product. Findings: The results showed (1) that there was no balance between theory and practice; (2) the validation test found that the objectives, content of the material, and learning presentations in terms of content and language were very good, while the appearance was classified as good; (3) the final product test shows the results of the student portfolio assessment are very good; (4) revision of the final product is carried out in the section on the instructions for using the DMC learning model. Implications: The development of this project-based DMC learning model is only developed in an effort to improve the quality of digital learning marketing. Practical implications: DMC practice is only internalized through -based DMC learning project. Originality/value: The resulting product can be used as a digital learning reference marketing to grow students' DMC skills, so that obtained learning outcomes in accordance with the objectives of MBKM. Paper type: Research paper